Study of High-Transverse-Momentum Higgs Boson Production in Association with a Vector Boson in the qqbb Final State with the ATLAS Detector - Aad, G.; Abbott, B.; Abbott, D.C.; Abed Abud, A.; Abeling, K.; Abhayasinghe, D.K.; Çetin, Serkant Ali (American Physical Society, 2024)
This Letter presents the first study of Higgs boson production in association with a vector boson (V ¼ W or Z) in the fully hadronic qqbb final state using data recorded by the ATLAS detector at the LHC in proton-proton collisions at ?s = 13 TeV and corresponding to an integrated luminosity of 137 fb?1. The vector bosons and Higgs bosons are each reconstructed as large-radius jets and tagged using jet substructure techniques. Dedicated tagging algorithms exploiting b-tagging properties are used to identify jets consistent with Higgs bosons decaying into bb?. Dominant backgrounds from multijet production are determined directly from the data, and a likelihood fit to the jet mass distribution of Higgs boson candidates is used to extract the number of signal events. The VH production cross section is measured inclusively and differentially in several ranges of Higgs boson transverse momentum: 250–450, 450–650, and greater than 650 GeV. The inclusive signal yield relative to the standard model expectation is observed to be ? = 1.4+1.0?0.9 and the corresponding cross section is 3.1 ± 1.3(stat)+1.8?1.4(syst) pb. © 2024 CERN, for the ATLAS Collaboration.
Keywords: Signal Processing; Tellurium Compounds; Atlas Detectors; B-Tagging; Final State; Hadronics; Higgs Boson; Integrated Luminosity; Proton Proton Collisions; Substructure Technique; Transverse Momenta; Vector Boson; Bosons; Article; Boson